Asperinsuterpenes A–C from the Fungus Aspergillus insuetus BTBU20220155 - Xinjun Zhang; Fuhang Song; Jiahui Han; Long Wang; Linlin Ma; Xiuli Xu (Journal of Fungi, 2024)
Three new meroterpenoids, asperinsuterpenes A–C (1–3), and eight previously reported natural products, namely asnovolin I (4), (2′E,4′E,6′E)-6-(1′-carboxyocta-2′,4′,6′-triene)-9-hydroxydrim-7-ene-11,12-olide (5), (2′E,4′E,6′E)-6-(1′-carboxyocta-2′,4′,6′-triene)-11,12-epoxy-9,11-dihydroxydrim-7-ene (6), cinereain (7), carnequinazolines A and B (8 and 9), carnemycin B (10), and stromemycin (11) were isolated from the fungus Aspergillus insuetus, strain BTBU20220155. The structures of the compounds were determined based on spectroscopic techniques, including 1D and 2D NMR, HRESIMS, and ECD experiments. The in vitro antimicrobial evaluation revealed that compounds 5 and 11 exhibited inhibitory activity against Candida albicans, with minimum inhibitory concentration (MIC) values of 12.5 and 25 μg/mL, respectively. These findings suggest that A. insuetus is a promising source of bioactive natural products with potential applications in antifungal therapy.